A socio-technical transitions perspective for assessing future sustainability following the COVID-19 pandemic. Issue 1 (10th December 2020) - Wells, Peter; Abouarghoub, Wessam; Pettit, Stephen; Beresford, Anthony
Abstract: This policy brief argues that the COVID-19 pandemic exposes the fractures in the contemporary global socio-technical order and offers the prospects of several different alternative futures. The policy brief explores the pandemic through the lens of the multi-level perspective on socio-technical transitions. The pandemic is framed as a meta-transition event at the landscape level of unprecedented scale, pace, and pervasiveness such that it permeates all socio-technical regimes simultaneously. The prospects for the future are then defined on a matrix that compares the strength of civil society and that of economic structures. The result is four distinct scenarios that are linked to contemporary discourses on socio-economic futures: business as usual; managed transition; chaotic transition; and managed degrowth. The scenarios are presented as a starting point for policy discussion and the engagement of societal actors to define social and economic possibilities for the future, and the implications that the different futures would have for ecological burdens. It is concluded that the COVID 19 pandemic can act as a catalytic event in which the legitimacy and efficacy of existing economic and political structures will be challenged and reshaped, and hence is an opportunity to redefine the ecological burdens our activities create.